Tradition and the Translation of Democracy during the Transitional Period of Modern China (1895–1925). Issue 3 (2nd July 2016) - Major, Philippe
ABSTRACT: This article argues that Anglophone works on Chinese democracy have tended to build their analyses on assumptions that tradition is either (1) a premodern phenomenon unrelated to China's democratization process, (2) a hindrance that should be gotten rid of if China is to democratize, (3) a static phenomenon that cannot but appear antiquated with regard to a dynamic, fast-paced modern China, or (4) an object from which modern agents can freely draw. In order to challenge these assumptions, this article suggests that modernity and democracy were translated into a Chinese milieu already ripe with Gadamerian prejudices: prejudices that not only modified the meaning of modernity and democracy, but also provided the very conditions without which modernity and democracy would not have been meaningful or understood at all. Max Ko-wu Huang's work can contribute to our understanding of the role played by various traditions in the process of translating democracy during the transitional period of modern China (1895–1925).